ANGUSTIFOLIA, a Plant Homolog of CtBP/BARS Localizes to Stress Granules and Regulates Their Formation - Bhasin, Hemal; Hülskamp, Martin (Frontiers in Plant Science, 2017)
The ANGUSTIFOLIA (AN) gene in Arabidopsis is important for a plethora of morphological phenotypes. Recently, AN was also reported to be involved in responses to biotic and abiotic stresses. It encodes a homolog of the animal C-terminal binding proteins (CtBPs). In contrast to animal CtBPs, AN does not appear to function as a transcriptional co-repressor and instead functions outside nucleus where it might be involved in Golgi-associated membrane trafficking. In this study, we report a novel and unexplored role of AN as a component of stress granules (SGs). Interaction studies identified several RNA binding proteins that are associated with AN. AN co-localizes with several messenger ribonucleoprotein granule markers to SGs in a stress-dependent manner. an mutants exhibit an altered SG formation. We provide evidence that the NAD(H) binding domain of AN is relevant in this context as proteins carrying mutations in this domain localize to a much higher degree to SGs and strongly reduce AN dimerization and its interaction with one interactor but not the others. Finally, we show that AN is a negative regulator of salt and osmotic stress responses in Arabidopsis suggesting a functional relevance in SGs.